Concurrent Associations Between Trauma and Borderline Personality Organization in Emerging Adulthood - Aikaterini Malafanti; Vasiliki Yotsidi; Eleni Giannouli; Evangelia Paraskevadaki; Ioannis Malogiannis (Mediterranean Journal of Clinical Psychology)
Introduction: There is limited research on the role of traumatic experiences in the development of borderline personality organization (BPO), which is a level of personality pathology characterized by identity diffusion, primitive defenses, impairment in reality testing, aggression, and deficits in the internalization of moral values, according to Kernberg’s psychodynamic model. Even less research evidence exists on the role of adult trauma in BPO.